Lab to produce cash crop seeds - New Sunday Times, (2012)
KULlM: The first tissue culture laboratory established here aims to produce at least 50,000 seeds of cash crops such as banana and herbs for farmers in the northern development corridor, said Kedah Menteri Besar Datuk Seri Azizan Abdul Razak.